2023
DOI: 10.1093/ehjqcco/qcad051
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on delayed care of cardiovascular diseases in Europe: a systematic review

Yasmine Khan,
Nick Verhaeghe,
Brecht Devleesschauwer
et al.

Abstract: Aims Cardiovascular diseases (CVD) are the leading cause of death worldwide. The COVID-19 pandemic has disrupted healthcare systems, causing delays in essential medical services, and potentially impacting CVD treatment. This study aims to estimate the impact of the pandemic on delayed CVD care in Europe by providing a systematic overview of the available evidence. Methods and results PubMed, Embase and Web of Science were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…The negative impacts of the pandemic have been compounded by the rising cost-of-living crisis which may have further widened socioeconomic inequalities (10). One systematic review examining the impact of the COVID-19 pandemic on CVD related care (11) highlighted reduced and delayed CVD-related hospital admissions, except for cardiac arrests, and increased CVD mortality. However, a Swiss study of deprivation and CVD found that there were no changes in the relative patterning of inequalities resulting from the pandemic (12).…”
Section: Introductionmentioning
confidence: 99%
“…The negative impacts of the pandemic have been compounded by the rising cost-of-living crisis which may have further widened socioeconomic inequalities (10). One systematic review examining the impact of the COVID-19 pandemic on CVD related care (11) highlighted reduced and delayed CVD-related hospital admissions, except for cardiac arrests, and increased CVD mortality. However, a Swiss study of deprivation and CVD found that there were no changes in the relative patterning of inequalities resulting from the pandemic (12).…”
Section: Introductionmentioning
confidence: 99%
“… 11 There are also likely to be issues related to healthcare access and diagnosis following the COVID-19 pandemic, which led to reduced CVD admissions and increased CVD mortality. 12 Delayed or misdiagnosis contributes to inappropriate treatments or unnecessary evaluations. 13 14 Adverse outcomes such as hospitalisation or death may result from effective treatment not being received until the disease is more advanced.…”
Section: Introductionmentioning
confidence: 99%